The “Villas de Sesimbra” Aparthotel and The Importance of Training Low-Skilled Workers - Lopes, Albino; Romana, Fernando Acabado (Archives of Business Research, 2024)
This case study describes the complex process of qualifying accommodation employees at the “Villas de Sesimbra” aparthotel, in the context of an organizational change and the development of a prismatic structural configuration that favours leadership and management by teams, an organization who learns. This is, effectively, a case study of management and employee satisfaction based on the consolidation of the strategic “pillar”, par excellence, of People Management, constituted by “continuous and qualifying professional training, in practice” (Lopes, 2012), in relation to all 12-hotel staff (permanent and seasonal). By proceeding in this way, the hierarchical pyramid is considerably reduced, and may even nullify the tradition of maintaining indefinitely the organization of work based on low-skilled workers. As a result, it could evolve into project management. The qualification of these workers was assumed to be strategic by the administration, which also accepted a re-elaboration of the structure (from hierarchical centralization to evolving into a “prismatic” structure that would allow for success based on “project management”). Training would follow the “ANEFA” model, of on-the-job learning, according to the four skills considered as core (project - Saber+): (i) literacy (knowing more); (ii) citizenship (participation in business life); (iii) numeracy (mathematics for life); (iv) technology (judicious use of ICTs). The workers wrote their manual personalized work on the topic of “accommodation management”. Organizational reconversion increased management autonomy, with a dynamic focus on the events and company meetings market, while the effectiveness and productivity of accommodation workers increased, with them being hired as permanent workers and transferred to situation of multi-purpose employees, capable of serving tables and supporting breakfast services. Organizational change, developed as a function of resolving a single initial problem (Kotter, 1995; Weick and Quinn, 1999), in fact involved the entire structure and led it to a stage of organizational learning (Senge, 1990).